2020
DOI: 10.1021/acs.jnatprod.0c00893
|View full text |Cite
|
Sign up to set email alerts
|

Highly Oxidized Ellagitannins of Carpinus japonica and Their Oxidation–Reduction Disproportionation

Abstract: In the research on ellagitannin metabolism, two unique dehydroellagitannins, carpinins E (1) and F (2), bearing dehydrohexa­hydroxy­diphenoyl (DHHDP) and hydrated biscyclo­hexenetrione dicarboxyl ester (HBCHT) groups, were isolated from young leaves of Carpinus japonica. Upon heating in H2O or treatment with pH 6 buffer at room temperature, 1 and 2 afforded the reduction product 3, isocarpinin A, with an (R)-hexahydroxy­diphenoyl (HHDP) group, suggesting the occurrence of redox disproportionation of the (S)-DH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The chiral axis in HHDP may show different absolute configurations, ( R )- or ( S )-. Correspondingly, HHDP-containing tannins exist as two atropisomers [ 31 ]. From the perspective of organic stereochemistry, these two atropisomers are actually two diastereomers, some of which can be individually isolated from plants [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The chiral axis in HHDP may show different absolute configurations, ( R )- or ( S )-. Correspondingly, HHDP-containing tannins exist as two atropisomers [ 31 ]. From the perspective of organic stereochemistry, these two atropisomers are actually two diastereomers, some of which can be individually isolated from plants [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we recently reported that some ellagitannin HHDP groups were reductively metabolized from DHHDP groups in the leaves of Castanopsis sieboldii , Triadica sebifera , Carpinus laxiflora , and Carpinus japonica [15] . Moreover, amariin and isoamariin having 3,6‐DHHDP esters and carpinins E and F with 2,3‐DHHDP esters were spontaneously degraded to 3,6‐HHDP and 2,3‐HHDP groups, respectively, in aqueous solutions at pH 6 and room temperature, and the reactions of the DHHDP groups were suggested to be a reduction‐oxidation disproportionation [15b,c] …”
Section: Methodsmentioning
confidence: 99%
“…CH 3 CN was stable at room temperature, heating of the solution at 85 °C converted 8 into 6 without a reducing agent (Figure S3), which supports the metabolic conversion of the DHHDP group into the HHDP group. This reaction can be considered to occur via a reduction‐oxidation disproportionation caused by an intermolecular electron transfer [15c] …”
Section: Methodsmentioning
confidence: 99%